Roles and Mechanisms of Ferroptosis in Sorafenib Resistance for Hepatocellular Carcinoma - Liu R; Cui H; Li D; Guo X; Zhang Z; Tan S; Zhu X (Journal of Hepatocellular Carcinoma)
Ruyuan Liu,1,* Huanyu Cui,1,* Di Li,1 Xuefeng Guo,1 Zhengbao Zhang,1 Shengkui Tan,1,2 Xiaonian Zhu1 1Guangxi Key Laboratory of Environmental Exposomics and Entire Lifecycle Health, Guilin Medical University, Guilin, 541199, People’s Republic of China; 2Guangxi Clinical Medical Research Center for Hepatobiliary Diseases, the Affiliated Hospital of Youjiang Medical University for Nationalities, Baise, Guangxi, 533000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaonian Zhu, Guangxi Key Laboratory of Environmental Exposomics and Entire Lifecycle Health, Guilin Medical University, No. 1 Zhiyuan Road, Guilin, Guangxi, 541199, People’s Republic of China, Email zhuxiaonian0403@163.comAbstract: Hepatocellular carcinoma (HCC) is the most prevalent malignant tumor, characterized by a poor prognosis. In recent decades, both the incidence and mortality rates of HCC have risen sharply. Sorafenib has emerged as the first conventional drug approved by the US Food and Drug Administration for first-line treatment in advanced HCC patients due to its favorable safety profile. However, its effectiveness is severely hindered by acquired drug resistance, which leads to only approximately 30% of HCC patients benefited from sorafenib therapy. Sorafenib resistance involves various mechanisms that inhibit cellular uptake of iron and reactive oxygen species (ROS). Consequently, ferroptosis a novel form of cell death contingent upon the accumulation of intracellular iron and ROS plays a critical role in mediating sorafenib resistance through the Hippo YAP pathway or Keap1-Nrf2 system. This review aimed to comprehensively elucidate the mechanisms underlying sorafenib resistance in HCC, particularly focusing on ferroptosis and its pathways, to provide valuable insights into targeting ferroptosis or its pathways for sorafenib-resistant HCC treatment.Keywords: ferroptosis, sorafenib resistance, hepatocellular carcinoma, molecular mechanism